THE EFFECTS OF MECHANICAL STRESSES ON THE COMPARATIVE MICROLEAKAGE OF TWO DIFFERENT RESTORATIVE MATERIALS - Naghma Parveen; Bilal Ahmed (Journal of University Medical & Dental College, 2012)
ABSTRACT Objectives: To assess the effects of lateral mechanical stresses on the microleakage of resin modified glass ionomer and polyacids modified composites. Study design and settings: It was a comparative cross sectional study carried out jointly by Department of Dental Materials, Nishtar Institute of Dentistry, Multan and Department of Dental Materials, University Medical & Dental College, Faisalabad. Materials and methods: Fifty healthy, unrestored, extracted premolar teeth were collected and then randomly divided into two groups. Class V cavities were prepared at the cemento-enamel junctions and these teeth were restored with Fuji II.LC (GC America) and Dyract (Dentsply), 25 teeth in each group. Teeth from each group were subjected to 8400 cycle of lateral fatigue forces (49 N) at the occlusal half of the clinical crown in a machine. All the teeth were placed in 2% basic fuchsin dye for 24 hrs at 37°C. Teeth were then embedded in cold cure acrylic resin, sectioned longitudinally in–ISOMETA, and the dye penetration at the enamel and cementum margin were scored at 10 X magnification Stereo microscope. Results: Distinct leakage patterns were recorded. There was very little difference between the microleakage score of two materials at their incisal margins. But microleakage difference was greater for these two materials on gingival margins of these restorations, where Dyract showing better results. Conclusion: Among these two materials tested, Dyract showed lesser microleakage than Fuji II.LC.